Employment Protection in Dual Labor Markets: Any Amplification of Macroeconomic Shocks? - Lochner, Benjamin (The B.E. Journal of Macroeconomics, 2023)
This paper studies the effects of labor market duality in terms of employment legislation protection (EPL) on labor market volatilities. Modeling contractual heterogeneity through a gap in EPL of temporary and permanent workers (weakly protected temporary/highly protected permanent contracts), I simulate both supply and demand shocks in a New Keynesian model with unemployment. I find that unemployment fluctuations follow an inverted U-shape over the magnitude of the EPL gap: small EPL gaps amplify, while large EPL gaps dampen the reaction of unemployment. In a subsequent empirical analysis, I find that the model’s predictions are consistent with panel data for a large set of OECD countries. Uncovering the non-linear course of unemployment volatility helps reconcile previous divergent research results.<br